2020
DOI: 10.1155/2020/7241942
|View full text |Cite
|
Sign up to set email alerts
|

VSNL1 Promotes Gastric Cancer Cell Proliferation and Migration by Regulating P2X3/P2Y2 Receptors and Is a Clinical Indicator of Poor Prognosis in Gastric Cancer Patients

Abstract: Purpose. The aim of this study was to investigate the role of Visinin Like 1 (VSNL1) in the proliferation and migration of gastric cancer (GC) cells as well as its clinical prognostic significance. Methods. To this end, we evaluated VSNL1 expression in GC tissues and cell lines by real-time PCR and immunohistochemistry. To further explore the effects of VSNL1, a lentiviral vector expressing a short hairpin RNA (shRNA) against VSNL1 was constructed and transduced into the GC cell lines BGC-823 and SGC-7901. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The research concerning VSNL1 has mainly focused on neurological diseases such as Alzheimer’s disease and medulloblastoma [ 36 , 37 ]. VSNL1 has also been investigated in gastrointestinal tumors, where it promotes the rapid growth and metastasis of gastric cancer cells [ 38 ], lymph node metastasis, and the deterioration of colorectal cancer [ 39 ]. However, the VSNL1 function in CCA needs to be further analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The research concerning VSNL1 has mainly focused on neurological diseases such as Alzheimer’s disease and medulloblastoma [ 36 , 37 ]. VSNL1 has also been investigated in gastrointestinal tumors, where it promotes the rapid growth and metastasis of gastric cancer cells [ 38 ], lymph node metastasis, and the deterioration of colorectal cancer [ 39 ]. However, the VSNL1 function in CCA needs to be further analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Global P2Y2 inactivation impaired the purinergic and Cl - secretory responses in the airways (trachea), gallbladder, and intestines [ 55 , 68 ]. A comparison of P2Y2-KO to WT mice showed the most effects in trachea, and to lesser extent in the gallbladder and intestine [ 55 , 68 , 69 ]. The phenotype of P2Y2-KO mice suggests that the biological function of P2Y2 can be compensated by P2Y4 and P2Y6 receptors in other organs [ 55 , 68 ].…”
Section: Deletion Overexpression and Disorders Of P2y2mentioning
confidence: 99%
“…It inhibits the migration and invasion of squamous cell carcinoma, [17][18][19] whereas it promotes the proliferation, migration, and invasion of gastric cancer and neuroblastoma. 20,21 VSNL1 reportedly promotes CRC proliferation, migration, and invasion. 22 In the present study, we identified VSNL1 as a novel target gene of the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 95%
“…The role of VSNL1 in tumorigenesis is reportedly cancer type dependent. It inhibits the migration and invasion of squamous cell carcinoma, 17–19 whereas it promotes the proliferation, migration, and invasion of gastric cancer and neuroblastoma 20,21 . VSNL1 reportedly promotes CRC proliferation, migration, and invasion 22…”
Section: Introductionmentioning
confidence: 99%